The Influence Of Providing Rewards And Reinforcement On Stuedent Learning Outcomes In Class IV Mathematics At State Primary School 106143 Sukamaju School Year 2022/2023 - Abi, Antonius Remigius; Sitanggang, Paskah Afriani; Lumbanraja, Bogol; Regina Sipayung; Rumiris Lumban Gaol (MultiTech Publisher, 2023)
This study aims to determine the effect of giving rewards and reinforcement on student learning outcomes in mathematics in class IV at SD Negeri 106143 Sukamaju for the 2022/2023 academic year. In this study, researchers used quantitative methods. The population used was all students at SD Negeri 106143 Sukamaju with a sample of 31 students. Sampling using nonprobability sampling. The results of this study indicate that the results obtained from correlation test can be seen in the correlation coefficient of r (count) 0.689 ≥ r (table) 0.355, it can be concluded that the alternative hypothesis (Ha) is accepted, that is, there is a significant effect between reward and reinforcement on student learning outcomes at SD Negeri 106143 Sukamaju. It can also be seen from the results of the t-test where t (count)> t (table) is t (count) of 5.113 and t (table) of 2.042, then the hypothesis (Ha) is accepted. This shows that there is a significant positive effect between the provision of rewards and reinforcement and mathematics learning outcomes in class IV of SD Negeri 106143 Sukamaju for the 2022/2023 academic year.